Spatial and ecological variation in dryland ecohydrological responses to climate change: implications for management. Issue 11 (28th November 2016) - Palmquist, Kyle A.; Schlaepfer, Daniel R.; Bradford, John B.; Lauenroth, William K.
Abstract: Ecohydrological responses to climate change will exhibit spatial variability and understanding the spatial pattern of ecological impacts is critical from a land management perspective. To quantify climate change impacts on spatial patterns of ecohydrology across shrub steppe ecosystems in North America, we asked the following question: How will climate change impacts on ecohydrology differ in magnitude and variability across climatic gradients, among three big sagebrush ecosystems (SB‐Shrubland, SB‐Steppe, SB‐Montane), and among Sage‐grouse Management Zones? We explored these potential changes for mid‐century for RCP8.5 using a process‐based water balance model (SOILWAT) for 898 big sagebrush sites using site‐ and scenario‐specific inputs. We summarize changes in available soil water (ASW) and dry days, as these ecohydrological variables may be helpful in guiding land management decisions about where to geographically concentrate climate change mitigation and adaptation resources. Our results suggest that during spring, soils will be wetter in the future across the western United States, while soils will be drier in the summer. The magnitude of those predictions differed depending on geographic position and the ecosystem in question: Larger increases in mean daily spring ASW were expected for high‐elevation SB‐Montane sites and the eastern and central portions of our study area. The largest decreases in mean daily summer ASW were projected for warm, dry, mid‐elevation SB‐Montane sites in the central and west‐central portions of our study area (decreases of up to 50%). Consistent with declining summer ASW, the number of dry days was projected to increase rangewide, but particularly for SB‐Montane and SB‐Steppe sites in the eastern and northern regions. Collectively, these results suggest that most sites will be drier in the future during the summer, but changes were especially large for mid‐ to high‐elevation sites in the northern half of our study area. Drier summer conditions in high‐elevation, SB‐Montane sites may result in increased habitat suitability for big sagebrush, while those same changes will likely reduce habitat suitability for drier ecosystems. Our work has important implications for where land managers should prioritize resources for the conservation of North American shrub steppe plant communities and the species that depend on them.